Intercropping of Spinach With Bottlegourd as a Leafy Vegetables Under Different Planting Methods (Bangladesh Agronomy Journal, 2022)
Intercropping is the option of growing more crops in the same piece of land for additional profit and to mitigate the losses or failure of the main crop. Considering this view, an experiment was designed to observe the growth and yield performance of spinach as an intercrop with bottle gourd as leafy vegetable under various planting method to increase productivity and economic return. The study included four planting systems viz; broadcasting spinach with bottle gourd, line sowing spinach with bottle gourd, sole bottle gourd and sole spinach followed by RCB design with three dispersed replications. Based on the growth and yield performance with economic return, intercropping performed better than sole cropping. The higher bottle gourd equivalent yield (15.67 to 28.36 %) was obtained in line sowing of spinach with bottle gourd than sole bottle gourd. The land equivalent ratio (LER) showed a positive influence on intercropping systems compare to monoculture. The maximum gross return (Tk. 430000 ha-1), gross margin (Tk. 325000 ha-1) and BCR (4.10) was obtained from line sowing of spinach with bottle gourd. This practice could be able for better return with the same input and using the same area of land with minimum risk.Bangladesh Agron. J. 2021, 24(2): 91-97